2004
DOI: 10.1016/j.chroma.2004.08.055
|View full text |Cite
|
Sign up to set email alerts
|

Natural variability of the enantiomeric composition of bioactive chiral terpenes in Mentha piperita

Abstract: The variability of the enantiomeric distribution of biologically active chiral terpenes in Mentha piperita plants from different geographical origins was evaluated by solid phase microextraction-gas chromatography-mass spectrometry (SPME-GC-MS). The optimisation of some parameters (i.e. exposure temperature, extraction time and type of fibre) affecting SPME-extraction enabled relative standard deviations ranging from 4 to 13% to be achieved. The use of two different chiral stationary phases allowed to separate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 19 publications
2
21
0
Order By: Relevance
“…Specifically, these enantiomers were (-)-menthone, (-)-neomenthol, (-)-menthol, and (+)-isomenthol. This is in agreement with data previously found for a number of samples in our laboratory by employing solid phase microextraction (SPME) [19] as well as by other authors using different analytical techniques [20][21][22]. Although the peak areas obtained (Table 1) were similar when applying any of the set of values of the tested parameters, 208C and 3 min were finally selected as the PTV temperature and the purge time, respectively, since they provided acceptable areas also showing high effectiveness in solvent elimination.…”
Section: Resultssupporting
confidence: 93%
“…Specifically, these enantiomers were (-)-menthone, (-)-neomenthol, (-)-menthol, and (+)-isomenthol. This is in agreement with data previously found for a number of samples in our laboratory by employing solid phase microextraction (SPME) [19] as well as by other authors using different analytical techniques [20][21][22]. Although the peak areas obtained (Table 1) were similar when applying any of the set of values of the tested parameters, 208C and 3 min were finally selected as the PTV temperature and the purge time, respectively, since they provided acceptable areas also showing high effectiveness in solvent elimination.…”
Section: Resultssupporting
confidence: 93%
“…The present results agree with previous studies, which demonstrated that the toxicities of the essential oils extracted from various plant samples were mainly related to their major components. Barcelona (Spain) [67]. The plants grown in Norway showed the presence of menthol and menthone as the main compounds [68].…”
Section: Contact and Fumigant Toxicity Methodsmentioning
confidence: 99%
“…The order of elution for each enantiomer was assigned by comparison with authentic standards and is in concordance with those reported in bibliography using equivalent stationary phases. 9,12,13,16 The elution orders of (+) and (-) enantiomers of linalool and α-terpineol were obtained from previous reports with equivalent column (Table 5). 9,13 At this moment, we were able to determine the enantiomeric excess of six enantiomeric pairs: α-pinene, camphene, linalool, 4-terpineol, borneol and α-terpineol.…”
Section: Resultsmentioning
confidence: 99%
“…10 The analysis of enantiomers in an essential oil can be useful to determine their authenticity in those cases in which one of its components is present in a high enantiomeric purity, or exists in a specific enantiomeric ratio. 11,12 Moreover, the determination of chiral compounds can be used for defining chemotypes in aromatic plants and for establishing their geographical origin. 13 In addition to this, the enantiomeric ratio of terpenes can vary depending on the part of the plant in study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation